Clinical outcome comparison of laparoscopic radical antegrade modular pancreatosplenectomy vs. laparoscopic distal pancreatosplenectomy for left-sided pancreatic ductal adenocarcinoma surgical resection - Niu, Nan; He, Yuhui; Mou, Yiping; Meng, Sijia; Xu, Peng; Zhou, Yucheng; Jin, Weiwei; Lu, Chao; Xu, Yunyun; Zhu, Qicong; Xia, Tao (Frontiers in Surgery, 2022)
Background Laparoscopic radical antegrade modular pancreatosplenectomy (LRAMPS) is a validated surgical treatment for patients with left-sided pancreatic ductal adenocarcinoma (PDAC). In addition, laparoscopic distal pancreatectomy (LDPS) has purported benefits. However, there is a limited analysis comparing the results between LRAMPS and LDPS. Thus, this study aims to compare the short-term and long-term outcomes of patients who underwent LRAMPS and LDPS for PDAC treatment. Methods Patients with left-sided PDAC that underwent LRAMPS or LDPS from 2015 to 2021 were retrospectively identified. Demographic and clinic pathologic data were collected. Disease-free survival (DFS) and overall survival (OS) probabilities were obtained. Results The number of lymph nodes retrieved was significantly greater in the LRAMPS group than in the LDPS group. Several clinicopathological factors, including CA19-9 levels greater than 37 U/ml, positive lymph nodes, moderate to poor tumor differentiation, and peripancreas fat invasion, were associated with DFS. Moderate with poor tumor differentiation was associated with poor DFS (HR 0.568; 95% CI 0.373–0.921; P = 0.021). Levels of CA19-9 greater than 37 U/ml, CEA levels greater than 5 μg/ml, larger tumor size, positive lymph nodes, moderate with poor tumor differentiation, peripancreas fat invasion, and adjuvant chemotherapy were all associated with OS. LRAMPS nearly improved OS but did not reach statistical significance. Serum carcinoembryonic antigen (CEA) levels greater than 5 ug/ml (HR 1.693; 95% CI 1.200–1.132; P = 0.001), and positive lymph nodes (HR 2.410; 95% CI 1.453–3.995; P = 0.001) were independently associated with poor OS. Treatment with adjuvant chemotherapy was associated with improved OS (HR 0.491; 95% CI 0.248–0.708; P = 0.001). Conclusions The LRAMPS procedure achieved comparable results to standard LDPS in terms of postoperative outcomes. Treatment with chemotherapy is important for the prognosis of patients with left-sided pancreatic cancer.